2009
DOI: 10.1155/2009/897424
|View full text |Cite
|
Sign up to set email alerts
|

Extensional Seismogenic Stress and Tectonic Movement on the Central Region of the Tibetan Plateau

Abstract: Various earthquake fault types, mechanism solutions and stress fields, as well as GPS and geothermal data are analyzed for the study of the crustal movements on the Tibetan plateau and their tectonic implications. The results show that a lot of the normal faulting type-event concentrated at altitudes greater than 4000 m on the central Tibetan plateau. The altitudes concentrating normal faulting type-events can be zoned two parts: the western part, the Lhasa block, and the eastern part, the QiangtangChangdu reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The block and fault physical parameters are listed in Table 1 along with related studies (Zhang et al 1995;Liu et,al. 2003;Xu and Zhao, 2009;Jiang et al 2009;Wang, 2005), in which Young's modulus of the fault is 1/3 of the blocks (Zhu et al, 2015). The triangular surface element PLANE 182 was used to divide the mesh, accurately simulating the irregular model.…”
Section: Finite Element Model Construction and Parameter Selectionmentioning
confidence: 99%
“…The block and fault physical parameters are listed in Table 1 along with related studies (Zhang et al 1995;Liu et,al. 2003;Xu and Zhao, 2009;Jiang et al 2009;Wang, 2005), in which Young's modulus of the fault is 1/3 of the blocks (Zhu et al, 2015). The triangular surface element PLANE 182 was used to divide the mesh, accurately simulating the irregular model.…”
Section: Finite Element Model Construction and Parameter Selectionmentioning
confidence: 99%
“…These faults were regarded as weak zones, with widths of 6 km. The block and fault physical parameters are listed in Table 1 along with related studies (Zhang et al, 1995;Liu et al, 2003;Wang, 2005;Xu and Zhao, 2009;Jiang et al, 2009), in which Young's modulus of the fault is 1/10 of the blocks (Zhu et al, 2015). The triangular surface element PLANE182 was used to divide the mesh, accurately simulating the irregular model.…”
Section: Finite Element Model Construction and Parameter Selectionmentioning
confidence: 99%
“…(2004) provided some useful constraints on the surface displacement, and they found that there is a very low tectonic denudation rate (near‐zero levels), and the tectonic activity is weakening in the central plateau (30°N–33°N, 82°E–92°E; 35°N–36°N, and 85°E). In addition, the thrust faults associated with strong compressive stresses are almost all located on the edges of the plateau (Xu & Zhao, 2009), which are beyond the TP boundary of this study, so the seismic energy accumulation and release processes are considered to have less of an effect on the tectonic displacement of the TP. Therefore, the central plateau is expected to be stable, with little vertical deformation.…”
Section: Observations and Models Of The Hydrological Variations And Crustal Displacementmentioning
confidence: 99%